Emerging Effects of Sevelamer in Chronic Kidney Disease - Ryota Ikee; Masataka Tsunoda; Naomi Sasaki; Naritsugu Sato; Nobuo Hashimoto (Karger Publishers, 2013)
Sevelamer, a non-absorbable anion exchange resin, is used to control hyperphosphatemia in chronic kidney disease (CKD) by binding to dietary phosphate in the gastrointestinal tract. Lipid-lowering effect is a widely recognized pleiotropic effect of sevelamer. In addition, many studies have reported that sevelamer leads to reduced vascular calcification compared with calcium-containing phosphate binders, which is attributed to the improved lipid profiles and decreased calcium load. In addition, recent studies have suggested novel pleiotropic effects on bone structure, inflammation, oxidative stress, anemia, fetuin-A, and trace element metabolism in CKD patients. All of these effects have the potential to suppress the development/progression of cardiovascular lesions and reduce mortality. This review summarizes novel findings from recent studies and discusses the potential pleiotropic effects of sevelamer on non-traditional cardiovascular risk factors in CKD patients.